Saberes construídos em projeto de prevenção ao abuso de drogas: subsídios para formação do educador - Robaina, José Vicenti Lima (Universidade do Vale do Rio do Sinos, 2007)
The thesis entitled Knowledge Constructed in Drug Abuse Prevention Project: A subsidy for teacher education is a qualitative research aiming at the analysis of the development of drug prevention programs at schools as a means to aid teacher education based on knowledge co-constructed by the segments involved in the process: teachers, parents, adolescents and other professionals working in such programs. Drug addiction (Carlini, Bucher, Tiba, Zagury, Vizzolto, Santos and Asinelli-Luz), teacher education (Zeichner, Nóvoa and Moraes) and knowledge (Tardif and Gauthier – teachers – and Charlot – adolescents) form the founding axis of the research. After studying some drug prevention projects, the project Escola Vida has been chosen for in-depth analysis due to relevant results exerted within the community. Nine interlocutors have been interviewed: 3 teachers, 3 adolescents and 3 members of the school community. For data treatment content analysis was used. The premise of the confirmed thesis was that schools that
Keywords: adolescentes; educadores; escola; formação continuada; formação inicial; prevenção ao abuso; saberes docentes; drogas; adolescents; drug abuse; prevention projects; qualification of teachers; school; teaching knowledge; drug prevention; Ciências Humanas